Problematika Pengembangan Potensi Wisata Subak Sebagai Agrowisata Di Subak Anggabaya Kelurahan Penatih Kota Denpasar - Ni Putu Sri Anggraeni; I Nyoman Sukma Arida (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2018)
This study aims to determine the obstacles in developing Subak Anggabaya as Agro tourism in Denpasar City. Data collection techniques used in this study are observations, interviews, and documentation studies, with data analysis techniques using Internal Factor Analysis (IFAS) and External Factor Analysis (EFAS) analysis techniques to identify obstacles in developing of Subak Anggabaya as Agro Tourism in the City Denpasar. The result of this research stated that the barriers in the development of Subak Anggabaya as agro tourism are the absence of formal management from institutions such as POKDARWIS (tourism related group in village community); the lack of awareness from the community about tourism potentialities in their area; the community has not been able to take significant steps/approaches in developing the tourism potentialities in their place; the absence of local tour guides; the similarity in developing new tourist attractions and the issues of land alteration that may threaten the existence of Subak Anggabaya. Keywords: obstacles, Internal Factor, External Factor of Agro Tourism, Subak Anggabaya